Effect of initial coal particle size on coal liquefaction conversion. (2016) - Heydari, Mehran; Rahman, Moshfiqur; Gupta, Rajender
In coal liquefaction process initial coal particle size can be considered as one of the important process parameters. In this work, particles of coal are prepared by pulverisation and separation into different particle size ranges below 45 to 1, 000 µm. Since conventional batch autoclave is not suitable for short contact time experiments, as the time required for the autoclave to reach the reaction temperature can be substantial, the liquefaction runs were investigated with a rapid injection reactor designed specifically for investigating the effect of initial particle size on liquefaction conversion. A Canadian coal was examined in a tubular bomb reactor in presence of tetralin at 400°C for a short reaction time (5 min) with pressure of 6 MPa under nitrogen atmosphere. The results indicated that total conversion obtained during the liquefaction changed according to the different particle size, and optimum particle size (150-212 µm) was detected for the liquefaction condition. [Received: November 27, 2014; Accepted: August 22, 2015]